Brand resilience : managing risk and recovery in a high-speed world - Copulsky, Jonathan R. (New York, NY : Palgrave MacMillan, 2011)
'As the recent Toyota and Tiger Woods scandals illustrate, brand reputation is more precarious than ever before. True and false information spreads like wildfire in the vast and interconnected social media landscape and even the most venerable brands can be leveled in a flash-by disgruntled customers, competing companies, even internal sources. Here, veteran marketing executive Jonathan Copulsky shows companies and individuals how to play brand defense in the twenty-first century. Five Signs that You Need to Pay More Attention to the Possibility of Brand Sabotage: A group of uniformed employees posts embarrassing YouTube videos, in which they display unprofessional attitudes towards their work. One of your senior executives publicly blames a supplier for product defects, even though they predate your relationship with the supplier. Your competitor's ads trumpet their solution to the performance problems associated with your most recent product. A customer unhappy with changes made to your product design launches a Facebook group, which attracts 5,000 fans. Your outsource partner is prominently featured in numerous blogs and websites describing allegations of worker mistreatment and workplace safety hazards'--
Includes bibliographical references and index.
Keywords: Branding (Marketing); Brand name products; Success in business